Further validation of the internet addiction test: Psychometric characteristics in a portuguese university sample. (13th April 2021) - Bento, C.; Pereira, A.T.; Marques, C.; Mota, D.; Macedo, A.
Abstract : Introduction: The Internet Addiction Test (IAT) is a 20-item, self-reported questionnaire that measures the presence and severity of Internet addiction which is an increasing problem in adolescents. Although a Portuguese version IAT has been validated in adults, its psychometric properties have never been evaluated before, in adolescents. Objectives: To analyse the reliability and construct and concurrent validity of the IAT in a Portuguese adolescent sample. Methods: 772 adolescents (53.5% girls), mean aged 13.21±2.246, answered the Portuguese versions of the IAT and the Portuguese versions of validated scales to evaluate: Cyberbullying, Game Addiction, Agressivity and Anxiety, Depression Scales. To study the temporal stability, 377 (60.5% girls) respondents answered the questionnaires again after approximately four-six weeks. The total sample was aleatory splitted to realize the exploratory and the confirmatory factor analyses. Results: Exploratory and confirmatory factor analyses supported a second order two-factor structure - "Isolation and Social Commitment" and F2-"Negligence and Functional Commitment". The χ2/df value was 2.260 and had a significant p value; it had the lowest RMSEA score = .074 (p< .001) and it had the highest TLI (.980) and CFI (.905). IAT mean scores were no different between genders [Girls=29.25±18.775 vs. Boys: 30.85±17.929, p=.405]. The Cronbach's alphas were > .85. Pearson correlation between the test and the re-test was r=.660. The IAT, video game addiction (r=.434), Cyberbullying (r=.383), anxiety (r=.209) and depression (r=.263) were significantly correlated (p<.001). Conclusions: The Portuguese IAT has good reliability and validity, showing to be an adequate instrument for measuring Internet Addiction symptoms in Portuguese Adolescents.